Synthesis of Cordierite ceramic using solid state reaction technique - Siti Nor Aizura Tuah (Universiti Malaysia Perlis, 2008)
In this project work, cordierite/ indialite phase was synthesized from three different ratios of powder mixture involved of kaolin, talc and alumina powder. The weight ratios of powder mixtures used in this project were 1:1:2, 1:1:3 and 2:2:5 which refers to alumina: talc: kaolin based on cordierite chemical composition. These powder mixtures were milled for two different milling time which are 6 h and 12 h using a planetary ball mill. Then the powder mixtures were sintered at 1400°C with two different soaking times 3 h and 6 h using high temperature muffle furnace. Sintered samples of the powder mixture were characterized by X-ray diffraction (XRD) and Scanning Electron Microscope (SEM). The XRD analysis showed α-cordierite (indialite) as a major phase existed in the samples milled for 6 h which sintered at 1400°C for 6 h soaking time. However, samples milled for 6 h sintered at 1400°C for 3 h soaking time the formation of cordierite phase were not observed but only secondary phases were formed including corundum, spinel, forsterite and cristobalite. Meanwhile, samples milled for 12 h sintered at the same temperature for 3 h and 6 h soaking time both showed α- cordierite (indialite) as a major phase existed. This experiment shows that, cordierite phase can be produced through simple milling and sintering method.